Navigating the Unknown: A Qualitative Exploration of Teachers’ Experiences on Leadership Rotation in Public Schools - Borlaza, Melanie; Ibañez, Zandro (Journal of Interdisciplinary Perspectives, 2025)
This study investigated the lived experiences and perceptions of elementary school teachers regarding leadership rotation in public schools. This study explored teachers' perspectives on leadership rotation in Digos City public schools, focusing on its effects on school stability, teacher morale, and instructional continuity. Utilizing a qualitative phenomenological research design, the study involved ten elementary school teachers from Digos City. Data gathered through in-depth interviews revealed three essential themes on teachers’ experiences with leadership rotation: instructional and policy changes, professional and emotional responses, and job stability and growth. In terms of coping mechanisms to ensure professional competencies under changing leadership, the identified themes included ensuring teaching stability, adapting to leadership transitions, and building peer support systems. Furthermore, teachers’ insights regarding the effects of leadership rotation on school management highlighted three key themes: strengthening school culture through leadership stability, mitigating the adverse impacts of leadership rotation, and adapting teaching practices to leadership changes. The findings emphasize the complexities and adaptive strategies teachers employ in response to leadership transitions. It is recommended that education stakeholders develop structured support programs to help teachers maintain professional stability and instructional quality during periods of leadership rotation.